2022
DOI: 10.1128/mbio.01888-22
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Inducible E3 Ligase RNF213 Facilitates Host-Protective Linear and K63-Linked Ubiquitylation of Toxoplasma gondii Parasitophorous Vacuoles

Abstract: Globally, approximately one out of three people become infected with the obligate intracellular parasite Toxoplasma. These infections are typically asymptomatic but can cause severe disease and mortality in immunocompromised individuals. Infections can also be passed on from mother to fetus during pregnancy, potentially causing miscarriage or stillbirth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 79 publications
2
23
0
Order By: Relevance
“…Ubiquitination of the PVM is a marker for parasite clearance in IFNγ-activated human cells (Clough et al ., 2016; Yao et al ., 2021; Hernandez et al ., 2022; Matta et al ., 2022). We therefore assessed if deletion of GRA57, GRA70 or GRA71 leads to differences in ubiquitination of the PVM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ubiquitination of the PVM is a marker for parasite clearance in IFNγ-activated human cells (Clough et al ., 2016; Yao et al ., 2021; Hernandez et al ., 2022; Matta et al ., 2022). We therefore assessed if deletion of GRA57, GRA70 or GRA71 leads to differences in ubiquitination of the PVM.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has found that RNF213, an IFNγ-induced host E3 ubiquitin ligase, mediates the majority of ubiquitin recruitment to both RH and PRU Toxoplasma vacuoles in HFFs (Hernandez et al ., 2022; Matta et al ., 2022); however, the target of this ligase is currently unknown. The observation that GRA57/GRA70/GRA71 deletion leads to reduced ubiquitination of the PV poses the intriguing question of whether the complex is required for RNF213 recruitment, is a direct target of ubiquitination, or is responsible for correct positioning of an RNF213 target at the PV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite a few host ubiquitin ligases, such as leucine-rich repeat and sterile α-motif containing 1 (LRSAM1), Parkin, Ring finger protein 166 (RNF166), RNF213, Ariadne RING-BetweenRING-RING (RBR) E3-ubiquitin protein ligase 1 (ARIH1), SMAD-specific E3-ubiquitin protein ligase 1 (Smurf1), and Skip-Cullin-F-box protein 2 containing complex (SCF FBXO2 ) are reported to decorate pathogen or pathogen-containing vacuoles with a variety of ubiquitin chain topologies (8,9,(11)(12)(13)(14)(15)(16)(17)(18). Notably, in particular, LRSAM1 through auto-ubiquitination possibly generates a robust ubiquitin signal around the bacteria to recruit the autophagic machinery (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Virulent type I strains are largely resistant to this pathway, while types II and III are susceptible (27), although the basis for this difference is unknown. Recent studies identified the E3 ubiquitin ligase RNF213 as a candidate for mediating early ubiquitination of T. gondii- containing vacuoles in IFN-γ treated A549 cells (30). The IFN-γ signaling and noncanonical ATG pathways are partially connected by ISG15, which is required for maximal recruitment of ATG adaptors and also interacts with RNF213 (28).…”
Section: Introductionmentioning
confidence: 99%